The unbeatable Squirrel Girl. Vol. 7, I've been waiting for a squirrel like you - North, Ryan, 1980- (Marvel Worldwide, 2018)
Doreen Green and Nancy Whitehead enter a programming competition, but don't realize that the prize is a trip to Savage Land. Squirrel Girl then finds herself fighting dinosaurs--including a dinosaur version of Ultron. Includes an exclusive zine, art from "Garfield" creator Jim Davis, and letters from loyal readers.